1986
DOI: 10.1002/ardp.19863191209
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen an 1.4‐Naphthochionen, 15. Mitt. Reaktion von 2‐ und 3‐Chlor/Bromjuglonderivaten mit methanolischer Lauge (Teil 1: Monomere Produkte)

Abstract: Die 2-und 3-Chlor-bzw. Bromjuglone 1-4 reagieren in methanolischer Natronlauge nicht regiospezifisch zu den entsprechenden Hydroxyjuglonen 5 und 6, sondern uber die intermediar gebildeten Methoxyderivate 7 und 8 zu Gemischen aus 5 und 6 rnit unterschiedlicher Regioselektivitat. Die analoge Reaktion der 2.3-Dichlor-bzw. Dibromjuglonderivate 14 und 15 fiihrt stets zu gleichen Gemischen aus 16a/b und ' I7a/b, die rnit Bu,SnH in einem Schritt strukturbeweisend in 7 bzw. 8 uberfuhrt werden. The 2-and 3-chloro-or br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Bromination of available hydroxyjuglone derivatives 7 and 8 in chloroform solution according to the work in [ 28 ] led to bromoquinones 9 and 10 in good yields, 92%. Subsequent treatment of quinones 9 and 10 in 1,4-dioxane with 0.2 M ethereal diazomethane solution and crystallization from MeOH gave a second pair of initial bromomethoxyjuglones 11 and 12 in yields 85% ( Scheme 2 ), which were identical to such compounds described in [ 29 ].…”
Section: Resultssupporting
confidence: 57%
“…Bromination of available hydroxyjuglone derivatives 7 and 8 in chloroform solution according to the work in [ 28 ] led to bromoquinones 9 and 10 in good yields, 92%. Subsequent treatment of quinones 9 and 10 in 1,4-dioxane with 0.2 M ethereal diazomethane solution and crystallization from MeOH gave a second pair of initial bromomethoxyjuglones 11 and 12 in yields 85% ( Scheme 2 ), which were identical to such compounds described in [ 29 ].…”
Section: Resultssupporting
confidence: 57%
“…Overall, the MS data, the absence of one aromatic proton and of one methoxy group in 2 (or one methylamino in 1), are in agreement with a terminal quinone moiety oxidatively cleaved and replaced by two carboxylic acids as reported in the literature. 15,16 Sufficient incorporation into paramagnetoquinones of 13 Clabeled precursor(s) took some media design efforts, since attempts failed in a minimal medium suitable for growth of and paramagnetoquinone production by strain ID145113 (see Experimental Section). We thus resorted to remove and/or replace individual components from the complex AF-A production medium in order to render it closer to a chemically defined medium.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Strain ID145113 was thus cultivated in 200 mL of AF-N medium containing 13 C-[U]-glucose. LC-MS analysis indicated that paramagnetoquinones were about 80% enriched in 13 C. Purification as described above led to 45 mg of the 1/2 mixture, which was then treated with H 2 O 2 to obtain 13 C-labeled 5.…”
Section: Journal Of Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…o -Vanillin ( 12 ) was reduced via a Wolf–Kischner reduction to the corresponding phenol ( 13 ), which underwent a salcomine ( 14 ) oxidation to afford quinone 15 in 88% yield over two steps . The methoxy group (i.e., 15 ) was exchanged for an isopropoxy ( 16 , 74%) in view of the fact that isopropyl ethers can be directly converted to acetyl groups . A Diels–Alder reaction involving cyclopentadiene was employed to protect the double bond carrying the methyl group, which proceeded with total stereoselectivity (i.e., 17 ).…”
mentioning
confidence: 99%